Weierstrass function, finite state automata, and l-system - Koutsomichalis, Marinos (My University, 2026)
Exhibition of audio work "Weierstrass function, finite state automata, and l-system" at the "Audiosphere Sound Experimentation 1980-2020" group exhibition hosted at the National Museum Reina Sofia in Madrid ES, October 14 2020 - January 11 2021 https://www.museoreinasofia.es/en/exhibitions/audiosphere